Titik Impas dan Bauran Pemasaran Bunga Rosella pada UD Bali Gendis di Desa Dawan Kelod Kecamatan Dawan Kabupaten Klungkung - ARILA, JESSICA; USTRIYANA, I NYOMAN GEDE; LISTIA DEWI, IDA AYU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.3, Juli 2013, 2013)
ABSTRACT Break Even and Marketing Mix of Rosella Flowers at UD Bali Gendis in The Village Dawan Kelod, District of Dawan, Sub District of Klungkung The research was conducted from early November 2012 until the end of January 2013 with the aim to determine the break-even of business gained and marketing mix applied by UD Bali Gendis. The analysis applied is the analysis of Break Even Point (BEP) to determine how much break even earned, both in the form of rupiah breakeven, breakeven point in units and breakeven point based on the corresponding gains desired by companies. The other analysis is the marketing mix applied to the analysis of the 4P (Product, Price, Place, and Promotion). UD Bali Gendis has production beyond breakeven point obtained in which in the form of rupiah at Rp 20,313,277.73 and produced Rosella flower tea production above the breakeven point unit is equal to 1354.21 units with a unit selling price of Rp 15.000 per box. From the analysis of the marketing mix it was found that the products produced by UD. Bali Gendis including consumable products. Pricing method used is the method of cost plus pricing and distribution channel marketing using direct and indirect distribution. UD Gendis Bali promotion includes personal selling and mouth to mouth method. Keyword : business analysis, marketing mix, rosella, UD Bali Gendis
Keywords: business analysis; marketing mix; rosella; UD Bali Gendis